Internationalisation, cultural distance and country characteristics: a Bayesian analysis of SMEs financial performance - Majocchi, Antonio; Dalla Valle, Luciana; D’angelo, Alfredo (Journal of Business Economics and Management, 2014)
Relying on the accounting data of a panel of 403 Italian manufacturing SMEs collected over a period of 5 years, we find results suggesting that multinationality per se does not impact on the economic performance of international small and medium sized firms. It is the characteristics of the country selected, i.e. the political hazard, the financial stability and the economic performance, that significantly influence SMEs financial performance. The management implication for small and medium sized firms selecting and entering new geographic markets is significant, since our results show that for SMEs it is the market selection process that really matters and not the degree of multinationality. First published online: 08 Jul 2013